Assessment of evolutionary algorithms for optimal operating rules design in real Water Resource Systems. (July 2015) - Lerma, Néstor; Paredes-Arquiola, Javier; Andreu, Joaquín; Solera, Abel; Sechi, Giovanni M.
Abstract: Two evolutionary algorithms (EAs) are assessed in this paper to design optimal operating rules (ORs) for Water Resource Systems (WRS). The assessment is established through a parameter analysis of both algorithms in a theoretical case, and the methodology described in this paper is applied to a complex, real case. These two applications allow us to analyse an algorithm's properties and performance by defining ORs, how an algorithm's termination/convergence criteria affect the results and the importance of decision-makers participating in the optimisation process. The former analysis reflects the need for correctly defining the important algorithm parameters to ensure an optimal result and how the greater number of termination conditions makes the algorithm an efficient tool for obtaining optimal ORs in less time. Finally, in the complex real case application, we discuss the participation value of decision-makers toward correctly defining the objectives and making decisions in the post-process. Highlights: SCE-UA and Scatter Search are assessed in order to design optimal operating rules. An analysis of the parameters is carried out to determinate the best stop criteria. The analysis carried out shows the most influential parameters. SCE-UA algorithm, applied in real cases, seems to be the most efficient algorithm. A way to transmit results is presented in order to make the decision-making easier.